Perancangan Aksara Lontara Untuk Transliterasi Ejaan Van Ophuisjen (Ejaan Lama Bahasa Indonesia) - Abd. Aziz Ahmad; Baso Indra Wijaya Aziz (Seminar Nasional LP2M UNM, 2022)
Abstract. This study aims to study and design: 1) A valid prototype of Lontara script symbols 2) techniques for writing seven Lontara script symbols, namely; Dj=J, J=Y, TJ=C, Oe=U, Nj=Ny, Sj= Sy, Ch= Kh, which has been designed as a Lontara script for transliteration of Van Ophuisjen spelling (Indonesian old spelling). Methodologically, this research was carried out through research and development procedures, with field trials. In operationalizing this research, the procedure formulated by Borg and Gall was used. Data collection was carried out by distributing questionnaires to a number of students from the Faculty of Art and Design, Universitas Negeri Makassar. And who have filled out the research questionnaire as many as 59 students.. The results showed that, as many as 7 designs of the Lontara script, each of which had 5 alternative choices for respondents' answers through the oneline questionnaire, the results were as follows: for Dj achieved No. 1b (42.4%), the letter Tj won No. 2e (28.8%), for J won No. 3b (33.9%), Nj won No. 4a (33.9%), for the Sj won No. 5a (35.6%), the letter Ch won No. 6a (30.5%), for the Oe diacritic won No. 7a (42.4%). Based on the results of the interviews, the informants wanted the Lontara script to be developed for the sake of preserving the cultural heritage of our ancestors as local wisdom in written form. Keywords: Lontara Script, Transliteration, Van Ophuisjen spelling